Draft Annual Plan 1994-95 Tamil Nadu - Planning Commission (Planning Commission, 1993)
The annual plan for 1994-95 assumes significance as it will be the mid-year of the Eighth Plan and the cumulative performance at the end of 1994-95 will largely determine the success of the Eighth Plan. Tamil Nadu has made a good beginning in the first year (1992-93) of the Plan and it is a matter of satisfaction that the plan expenditure during 1992-93 was Rs. 1935 Crores which represents an increase of Rs. 169 crores or 9.5 per cent over the approved plan outlay of Rs. 1,766 crores. The Agriculture Sector's performance was remarkably good and the foodgrains production reached the level of 84.55 lakh tonnes. Electricity generation was maintained al a fairly high level of 16,958 MU and the State did not impose, any power cut. Industrial production however received a set back but this was mainly due to macro economic factors operating at the national level such as recession and the credit squeeze over which the State has little control.
State Planning Commission
State Planning Commission